Digital Communication, Perceived Transparency, and Public Trust in a Government Infrastructure Project: Evidence from Karachi Mobility Project - Masood Ahmed; Nazar Hussain; Sanaullah Abro; Abdul Jabbar; Asma Kalhoro (International Journal of Emerging Multidisciplinaries: Social Science, 2026)
Digital communication plays an integral role in public-sector governance throughout the globe. Its role in improving public trust could rely on citizens' perceptions of the transparency of institutional communication. The study evaluates the relationship between digital communication and public trust in the Karachi Mobility Project (KMP) and the idea of perceived transparency as a mediator. The study relies on a quantitative cross-sectional survey of 200 respondents who knew about KMP, and examines the relationships between digital communication, perceived transparency and public trust using correlation, regression and bootstrapped mediation analysis. Citizens' perceptions are also complemented by an objective content analysis of the official KMP digital communications, which analyses how much transparency-oriented information is visible in the communication relating to a project. The results suggest that digital communication is positively related to perceived transparency and public trust and that perceived transparency makes a significant contribution to the relationship between communication and trust. Additionally, the content audit reveals inconsistencies in the amount of information that is provided on the project, problems, reactions of stakeholders, and grievance information in official communications. The present study also brings an important element to public administration research, putting perceived transparency, a key part of the public administration field, in the center of the discussion on how digital communication processes and their perceived transparency relate to public trust in the governance of infrastructure. The results indicate that public agencies would do well to not only see digital communication as a way to disseminate information or promote products, but as a form of government communication and public accountability, to report progress, recognize difficulties, and create a sense of public accountability.